2020
DOI: 10.21203/rs.3.rs-15447/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Geographic Information Systems and COVID-19: The Johns Hopkins University Dashboard

Abstract: Background: This article presents a single case study on the development of a GIS for global monitoring of coronavirus . For such concepts presented about GIS, its use and evolution in epidemic events and a presentation of the context of the current coronavirus outbreak and the meaningless results of consolidating a panel with reliable data.Methods: A single case study of a GIS in continuous development with data sharing and comments from the scientific community was carried out. Because it is not a post-morte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…In comparison, the GIDEIMS provides more comprehensive disease information than other COVID-19 epidemic information systems. Compared with the geographic information system for global monitoring of COVID-19 established by Johns Hopkins University [103], whose initial data were collected from the World Health Organization (WHO), US Centers for Disease Control and Prevention (CDC), China CDC, European Centre for Disease Prevention and Control (ECDC), National Health Commission of China (NHC), and DXY (a Chinese health-focused social website), the GIDEIMS could provide a full picture of the worldwide situation of the COVID-19 epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, the GIDEIMS provides more comprehensive disease information than other COVID-19 epidemic information systems. Compared with the geographic information system for global monitoring of COVID-19 established by Johns Hopkins University [103], whose initial data were collected from the World Health Organization (WHO), US Centers for Disease Control and Prevention (CDC), China CDC, European Centre for Disease Prevention and Control (ECDC), National Health Commission of China (NHC), and DXY (a Chinese health-focused social website), the GIDEIMS could provide a full picture of the worldwide situation of the COVID-19 epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…The first traced case was detected on 17th November 2019 in Hubei in China [6]. At the time of writing this study in August 2020, over 23,318,415 cases have been reported in 188 countries and regions, resulting in 806,630 deaths, and the going reported recovery of 15,027,662 people [7]. Therefore, on 11 th of March 2020, the World Health organization (WHO) declared COVID-19 outbreak as a global pandemic.…”
Section: The Of Reactions Toward Covid-19 Pandemicmentioning
confidence: 99%
“…The disease is mainly a respiratory tract viral infection caused by newly emerging strains of coronaviruses. More than 60 million confirmed coronavirus disease 2019 (COVID-19) cases, including almost 1.5 million deaths, have been reported globally in 189 countries since its inception up to October 2022[ 1 ]. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) disease infection has mainly targeted the respiratory tract system.…”
Section: Introductionmentioning
confidence: 99%